The Effect of Lemon Ginger Candy on Emesis Complaints in Pregnant Women at the First Trimester - Maya Astuti; Fuadah Ashri Nurfurqoni; Eva Sri Rahayu; Fauzia Djamilus (Indonesian Journal of Global Health Research, 2023)
Ginger is a herbal ingredient that contains gingerol and shogaol substances that are proven to reduce nausea (emesis). Lemon contains vitamin C and has a fresh aroma that can increase freshness and help reduce nausea in pregnant women. trimester. Objective: The purpose of this study is to find out the effect of lemon ginger candy on emesis complaints in pregnant women in the first. Method: This study uses a pre and posttest design with control group approach. The research location is in PMB of the Kemang Health Center in Bogor Regency in June - November 2021. The study sample was pregnant women in the first trimester who experienced nausea and vomiting. Sampling was carried out by purposive sampling techniques, with a sample of 30 people in the intervention group and 30 people in the control group. Pre-research begins with product trials, organoleptic tests and candy content tests. The intervention group consumed 5 grains of lemon ginger candy per day weighing @ 1 gram. Ten grams of lemon ginger candy contains 3 grams of ginger, 1.6 mg of vitamin C and 31.2 calories. Data collection was in the intervention and control group using the PUEQ questionnaire (Pregnancy Unique Quantification of Emesis and Nausea). Results: To determine the effectiveness of ginger candy consumption on the intensity of nausea and vomiting using the Mann-Withney test to determine the effectiveness of lemon ginger candy against complaints of emesis of pregnant women in the first trimester obtained a result of p < 0.05; there was a significant difference between the control group and the intervention group. Significant differences appeared from day 6 and day 7 of the intervention. Conclusions: Lemon ginger candy can be used as an herbal ingredient to reduce nausea in pregnant women.